2019年1月に北の浦（リュツォホルム湾・東南極）で採集された魚類の記録 - 西澤, 秀明; ニシザワ, ヒデアキ; 市川, 光太郎; イチカワ, コウタロウ; 浅井, 咲樹; アサイ, サキ; 荒井, 修亮; アライ, ノブアキ; 三田村, 啓理; ミタムラ, ヒロミチ; 宮本, 佳則; ミヤモト, ヨシノリ; et al. (国立極地研究所, 2019)
漁業活動や環境変化による南極海洋生態系への影響を評価する上で，魚類相のモニタリングを継続的におこなうことが求められる．2019 年1 月に北の浦（リュツォホルム湾・東南極）でナンキョクカジカ亜目Notothenioidei の魚類計5 種，52 個体を採集した．最も多く採集されたのはショウワギスTrematomus bernacchii（39 個体）であり，次に多く採集されたのはヒレトゲギスT. pennellii（10 個体）であった．本調査では過去の報告に比べてヒレトゲギスの採集が多く，ウロコギスT. hansoni の採集が少なかった（1 個体）．ショウワギスとヒレトゲギスについて体重と全長の関係を推定したところ，同じ全長の場合にはヒレトゲギスの体重が大きくなる傾向があった．また，体重は全長の3.23 乗（95% 信頼区間：3.003.46）に比例しており，アイソメトリー（等成長：3.33 乗）からの乖離は確認できなかった． Continuous monitoring of fish fauna is important for evaluating effects of fisheries and environmental changes on the Antarctic marine ecosystem. In January 2019, we collected 52 individuals of 5 species of notothenioid species in Kita-no-ura cove, Lützow-Holm Bay, East Antarctica. The emerald rockcod Trematomus bernacchii was the most dominant (N＝39), while the sharp-spined notothen T. pennellii was the second most common species (N＝10). The number of T. pennellii was larger, but the number of T. hansoni (N＝1) was smaller than previous studies. The relationship between body weight and total length of T. bernacchii and T. pennellii indicated that the body weight of T. pennellii tends to be higher than that of T. bernacchii of equal total length. Body weight is in proportion to total length to the power of 3.23 (95% confidence interval: 3.003.46); therefore, the deviation from isometry, the power of 3.33, was not observed. departmental bulletin paper